Pengembangan Bahan Ajar Strukturalisme Genetik untuk Pengkajian Prosa di Perguruan Tinggi (Tinjauan pada Karya Okky Madasari) - M. Ghufroni An’ars; M. Yanuardi Zain (LPPM STKIP PGRI Bandar Lampung, 2022)
The theory of genetic structuralism appears as a theory with a broad scope because it considers aspects outside the text. This breadth of coverage is often considered a problem in studying genetic structuralism, especially in the practice of studying prose in universities. However, the theory of genetic structuralism can be operated more simply, while still taking into account the limitations given by Goldmann. It was this simplification idea that prompted the preparation of the teaching material